Analisis Potensial Ekonomi di Daerah Ogan Komering Ulu, Provinsi Sumatera Selatan - Mauliyanti, Anita (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
In the order to achieve the objectives of regional economic development, development policies that are based on regional characteristics (endogenous development) are needed, using local resource potential. Identification of potential economic sectors is a necessity for the optimization of the process and the success of the intended economic development. From the calculation of the LQ method data, it was found that Ogan Komering Ulu District had six potential economic sectors which were supporting economic growth in Ogan Komering Ulu District of South Sumatra Province.